Pregabalin in acute and chronic pain - Dalim Kumar Baidya; Anil Agarwal; Puneet Khanna; Mahesh Kumar Arora (Wolters Kluwer Medknow Publications, 2011)
Pregabalin is a gamma-amino-butyric acid analog shown to be effective in several models of neuropathic pain, incisional injury, and inflammatory injury. In this review, the role of pregabalin in acute postoperative pain and in chronic pain syndromes has been discussed. Multimodal perioperative analgesia with the use of gabapentinoids has become common. Based on available evidence from randomized controlled trials and meta-analysis, the perioperative administration of pregabalin reduces opioid consumption and opioid-related adverse effects in the first 24 h following surgery. Postoperative pain intensity is however not consistently reduced by pregabalin. Adverse effects like visual disturbance, sedation, dizziness, and headache are associated with higher doses. The advantage of the perioperative use of pregabalin is so far limited to laparoscopic, gynecological, and daycare surgeries which are not very painful. The role of the perioperative administration of pregabalin in preventing chronic pain following surgery, its efficacy in more painful surgeries and surgeries done under regional anesthesia, and the optimal dosage and duration of perioperative pregabalin need to be studied. The efficacy of pregabalin in chronic pain conditions like painful diabetic neuropathy, postherpetic neuralgia, central neuropathic pain, and fibromyalgia has been demonstrated.